A reflective approach in vocational training of future officers of the National Guard of Ukraine - Mirshuk, O. (Problems of Engineer-Pedagogical Education, 2021)
The article highlights the basic principles, rates and levels of the system of higher military education, types of control and intermediate certification of higher education. The sequence of training of a military specialist (based on the example of a future officer working with personnel) is revealed, which is divided into four stages: at the first stage – the level of tactics of the soldier in the relevant positions for service and combat tasks of the National Guard of Ukraine, their activities as part of detachments and guards; at the second stage – the level of the division commander or sergeant platoon leader, the beginning of the study and mastery of combat and tactical actions of the platoon, improving the training of the division commander; at the third stage – the level of the platoon commander’s completion of mastering the tactical and servicecombat actions of the platoon in the course of performing assigned tasks, studying tactical and servicecombat actions of the company, improving and consolidating training skills for the position of the platoon commander; at the fourth stage – gaining theoretical knowledge and practical skills in performing the duties of the deputy company commander for the work with personnel. The role of military practice and internships, which are the logical conclusion of each stage of training in the formation of the professional subject position of higher education students and are purely reflective and evaluative in nature, is clarified. The views of domestic and foreign scientists on the reflexive approach in the educational process are considered. The variant of applying the reflective approach while training cadets of the National academy of the National Guard of Ukraine and advice to scientific and pedagogical workers concerning the formation of the maintenance of educational components and internship programs are offered. General conclusions are made about the proposed reflexive approach in the process of training future officers, which is the main tool in the self-control of higher education students, an indicator of future officers’ own activity with the awareness of their actions, individual and professional qualities, level of their professional development and self-determination. The directions and prospects of further research are determined.